Methodological issues of science as a discourse - Ягодзінський, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
Scientific discourse as a phenomenon of Postmodern culture has been researched. The attention is mainly focused on methodological, social and cultural aspects of science as a discourse. It has been stated, that scientific discourse penetrates into the majority of social practices in information society.